Bibliometric Analysis of Artificial Intelligence - Rohimatun Nur’aeni; Rendy Zalsahra (Westscience Press, 2024)
Artificial Intelligence Bibliometric Analysis (AI) is a study involving quantitative measurement and evaluation of scientific literature on artificial intelligence. Relevant keywords in this analysis include